Cost-effectiveness analysis of second-line medical therapies in acromegaly: a real-life study - Venegas Moreno, Eva; Jiménez-Sánchez, Andrés; Remón-Ruiz, Pablo; Dios, Elena; Perea Cortés, Jaime; Hernández-Reina, Celia; Cano, David A.; Soto Moreno, Alfonso (Frontiers in Endocrinology, 2025)
IntroductionAcromegaly is an uncommon disease with important comorbidity and economic cost. Although the pharmacological cost of second-line treatment for refractory acromegaly has been theoretically analyzed, real-life studies are needed.ObjectivesTo assess the use of pasireotide and pegvisomant in a third-level center under routine clinical practice.MethodsAcromegaly patients that had been treated with pasireotide and/or pegvisomant were included in (A) a cross-sectional study (two years after starting these drugs) to analyze the cost of acromegaly, hormone replacement, and type 2 diabetes mellitus (T2DM) treatments, and the cost of surgery and radiotherapy; and (B) a retrospective cohorts study (May 2006—October 2024) to analyze efficacy, safety (adverse events, fasting glucose, glycated hemoglobin, and T2DM diagnosis), and dose evolution. Descriptive statistics were 10% trimmed means and standard deviation. Two-tailed hypothesis testing with Yuen’s t and Fisher’s test had a P < 0.05 significance.Results25 participants were included in the transversal study and 31 participants in the longitudinal study. A typical patient with a poorly granulated GH-producing adenoma underwent in-center surgery once and received radiotherapy. In the transversal study, total pharmacological cost was 34,139.29 (13,472.09) €/person/year, with 33,874.88 (13,468.36) €/person/year for second-line acromegaly drugs. Pasireotide displayed 9,423.26 €/person/year worth of savings (P = .12), reaching 30,415.98 €/person/year at high dose (P < 0.001). In the longitudinal study, pasireotide dose was reduced (P = .06) regardless of treatment modality. Pasireotide affected carbohydrate metabolism (P = .001), but the effect was generally mild.ConclusionsPasireotide was found to be a more cost-effective option in patients with first-line treatment failure.